PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI KARAKTER PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA NEGERI 14 MALANG - Ahmad Leowaldi; Maskuri Bakri; Mohammad Afifulloh (VICRATINA, 2022)
The purpose of this study was to determine the teacher's role in instilling character values in SMPN 14 Malang. This study uses a descriptive qualitative approach with the type of field research (field research) in the context of a case study. The subject of this research are the curriculum, teachers and students. Data The collection techniques used are observation, interviews, and documentation. This research was conducted with the aim of describing the planning of caracter education planting, the implementation of caracter education planting, and the application model of caracter education at SMPN 14 Malang. The results of this study are in school planning to design curriculum, teachers make learning tools, manage classes. and school environment. application of character values through example and habituation. the models used in instilling character values are contextual models, direct models, and cooperative models.